Multi-principal component Al-Co-Cr-Cu-Fe-Ni high-entropy alloy coating and preparation method thereof
By preparing multi-main components on the surface of titanium alloy Al-Co-CR-CU-FE-NI high-entropy alloy coating, using laser melting technology to ensure uniform ingredients and metallurgical combination The problem of poor anti -high temperature oxidation capacity achieves the effects of high hardness, excellent abrasion resistance and anti -high temperature oxidation.
Patent Information
- Application Number
- CN202411450765.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Titanium alloy has low surface hardness, poor wear resistance and poor high-temperature oxidation resistance, which leads to easy surface defects during service, affecting the reliability and safety of components.
The multi-main component Al-CO-CR-CU-FE-Ni high-entropy alloy coating is used to form coatings with high hardness, excellent abrasion resistance and anti-high temperature oxidation through specific Merbi and preparation methods. This coating consists of AL, CU, CO, CR, FE, Ni and other elements. It is prepared by laser melting technology to ensure that the coating component is uniform and combined with the matrix.
The surface hardness of the titanium alloy has been significantly improved, and the wear resistance and high-temperature oxidation resistance have also been optimized, significantly improving the reliability and safety of titanium alloy components.
Smart Images

Figure CN119332149A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy surface coating modification, and specifically relates to a multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating and a preparation method thereof. Background Art
[0002] Titanium alloy has low surface hardness, poor wear resistance, and poor resistance to high-temperature oxidation, which makes it easy to produce surface defects such as pits and notches during service. TC4 titanium alloy is a material that is extremely sensitive to surface damage. It is easy for fatigue cracks to expand rapidly at the damaged part, causing local fracture of the component, which in turn affects the reliability and safety of the component. Therefore, titanium alloy components in actual use often need to be subjected to surface strengthening treatment to improve their fatigue performance.
[0003] High-entropy alloys (HEA) are alloys formed by five or more equal or approximately equal amounts of metals. Due to their unique elemental composition, arrangement and interaction potential field, they exhibit high entropy effects in thermodynamics, slow diffusion effects in kinetics, lattice distortion effects in structure and cocktail effects in performance, and are easy to form simple single-phase solid solutions, including BCC structures, FCC structures and HCP structures. Therefore, high-entropy alloys exhibit excellent comprehensive properties, such as high strength / hardness, excellent high-temperature oxidation resistance, corrosion resistance, radiation resistance and wear resistance, and have broad application prospects under extreme service environment conditions.
[0004] The main methods for titanium alloy surface modification include chemical heat treatment, ion implantation, micro-arc oxidation, electroplating, thermal spraying, laser surface alloying and laser cladding, etc. Among them, laser cladding technology has high melting temperature and cooling rate, which can refine the cladding layer structure; and low dilution rate can reduce the mutual diffusion of elements between the cladding layer and the substrate, so that the cladding layer maintains the designed composition and achieves metallurgical bonding. It has unique advantages in the preparation of high entropy alloy coatings and has been widely used in titanium alloy surface modification.
[0005] In summary, it is urgent and necessary to provide a high-entropy alloy coating with high hardness, excellent wear resistance and high-temperature oxidation resistance to cope with the extreme service conditions of existing titanium alloy components. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating and a preparation method thereof. The coating prepared by the present invention has high hardness, excellent wear resistance and high temperature oxidation resistance.
[0007] In order to achieve the above object, the present invention provides a multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating, comprising the following molar ratios of metal elements:
[0008] Al:Cu:Co:Cr:Fe:Ni=0.7:0.3:1:1:1:1;
[0009] The raw materials of Al and Cu are metal powders; the raw materials of Co, Cr, Fe and Ni are CoCrFeNi alloy powders;
[0010] The molar ratio of Co, Cr, Fe and Ni in the CoCrFeNi alloy powder is 1:1:1:1;
[0011] By adopting the above technical solution, compared with directly using independent Co, Cr, Fe, and Ni powders, the powders can have better fluidity while making the composition of the obtained coating more uniform.
[0012] The present invention provides a method for preparing the above-mentioned multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating, comprising the following steps:
[0013] S1. Al powder, Cu powder and CoCrFeNi alloy powder were weighed according to the molar ratio and then ball-milled and mixed uniformly and dried to obtain a mixed powder;
[0014] S2. performing surface pretreatment on the titanium alloy substrate;
[0015] S3. The mixed powder is flatly pressed on the surface of the pretreated titanium alloy substrate, and then a high entropy alloy coating is obtained by laser cladding technology.
[0016] Preferably, the purity of each component in S1 is not less than 99.9wt.%, the powder particle size is 15-53μm, and all powders are spherical powders.
[0017] Preferably, the ball milling mixing in S2 is carried out using a high-energy ball mill; the parameters of the ball milling are: rotation speed 120 rpm, time 10 h, and ball-to-material ratio of 4:1.
[0018] Preferably, the drying process in S2 is carried out at a temperature of 80 to 100° C. and for a time of 1 to 2 hours.
[0019] Preferably, the surface is polished with sandpaper of 400 and 600 meshes in sequence, then rinsed and wiped with alcohol, and finally the treated substrate is placed in a drying oven at 60-80° C. and dried for 1-2 hours for later use.
[0020] Preferably, the prefabricated layer of powder in S3 has a thickness of 1 to 2 mm.
[0021] Preferably, the laser cladding parameters in S3 are: power P=1100W, scanning speed v=300mm / min, spot diameter D=4mm, defocusing amount is 13mm, pure Ar gas is used as protective gas in the cladding process, and the gas flow rate is 15L / min.
[0022] The beneficial effects of the present invention include at least:
[0023] 1) The multi-principal component high entropy alloy coating obtained by laser cladding of the present invention has a good macroscopic morphology, and the coating and the substrate achieve good metallurgical bonding.
[0024] 2) The multi-principal component high-entropy alloy coating obtained by laser cladding of the present invention has a uniform and dense microstructure, and is composed of a face-centered cubic (FCC) structure, a body-centered cubic (BCC) structure and a small amount of Laves reinforcement phase. The crystals are equiaxed crystals and columnar crystals. The performance is significantly improved compared to the substrate, and the hardness and wear resistance are significantly improved.
[0025] 3) The four main components of Co, Cr, Fe and Ni in equal molar ratios in the present invention can form a CoCrFeNi high entropy alloy with a single FCC phase. The addition of Cu element will cause the alloy structure to transform into the FCC phase, and the addition of Al element will cause the alloy structure to transform into the BCC phase. In the present invention, a certain amount of Al element and Cu element are added to form an optimal organizational morphology, so that the alloy obtains a better strength-plasticity match, so that the obtained coating has improved strength and plasticity while also improving strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a macroscopic morphology of the coating prepared in Example 1;
[0027] Figure 2 XRD diffraction patterns of the coatings prepared in Example 1 and Comparative Examples 1-2;
[0028] Figure 3 The SEM image of the coating prepared in Example 1;
[0029] Figure 4 This is a line graph of the hardness distribution of the coating and the substrate obtained in Example 1. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] Example 1
[0036] A multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating specifically comprises the following preparation steps:
[0037] (1) Weighing Al powder, Cu powder, and CoCrFeNi alloy powder to ensure that the molar ratio of Al:Cu:Co:Cr:Fe:Ni is 0.7:0.3:1:1:1:1; wherein the molar ratio of Co, Cr, Fe, and Ni in the CoCrFeNi alloy is 1:1:1:1;
[0038] The purity of the raw material powder is not less than 99.9wt.%, the powder particle size is 40μm, and all powders are spherical powders;
[0039] (2) The raw material powder is placed in a planetary high-energy ball mill and ball-milled for 10 h at a rotation speed of 120 rpm and a ball-to-material ratio of 4:1 to mix evenly; after the ball milling, it is dried at 90° C. for 1 to 2 h to obtain a mixed powder.
[0040] (3) Pretreatment of the titanium alloy substrate surface: Use 400 and 600 mesh sandpaper to polish the surface of the Ti-6Al-4V substrate to remove surface oxides and oil stains, then rinse and wipe with alcohol, and finally put the treated substrate into a drying oven at 70°C for 2 hours for use.
[0041] (4) The mixed powder in step (2) is flatly pressed on the surface of the titanium alloy substrate pretreated in step (3) to form a prefabricated layer with a thickness of 1.5 mm, and then a high-entropy alloy coating is obtained by laser cladding; wherein the parameters of the laser cladding are: power P = 1100 W, scanning speed v = 300 mm / min, spot diameter D = 4 mm, defocus amount is 13 mm, and pure Ar gas is used as the protective gas in the cladding process, and the gas flow rate is 15 L / min.
[0042] Figure 1 This is a macroscopic morphology of the coating prepared in Example 1;
[0043] Figure 3 This is a scanning electron microscope (SEM) image of the coating prepared in Example 1; it can be seen that the coating has a uniform and dense structure without obvious defects, and the grains are equiaxed crystals and columnar crystals.
[0044] Example 2
[0045] A multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating specifically comprises the following preparation steps:
[0046] (1) Weighing Al powder, Cu powder, and CoCrFeNi alloy powder to ensure that the molar ratio of Al:Cu:Co:Cr:Fe:Ni is 0.7:0.3:1:1:1:1; wherein the molar ratio of Co, Cr, Fe, and Ni in the CoCrFeNi alloy powder is 1:1:1:1;
[0047] The purity of the raw material powder is not less than 99.9wt.%, the powder particle size is 53μm, and all the powders are spherical powders;
[0048] (2) The raw material powder was placed in a planetary high-energy ball mill and ball-milled for 10 h at a rotation speed of 120 rpm and a ball-to-material ratio of 4:1 to mix evenly; after the ball milling, it was dried at 100° C. for 2 h to obtain a mixed powder.
[0049] (3) Pretreatment of the titanium alloy substrate surface: Use 400 and 600 mesh sandpaper to polish the surface of the Ti-6Al-4V substrate to remove surface oxides and oil stains, then rinse and wipe with alcohol, and finally put the treated substrate into a drying oven at 80°C for 2 hours for use.
[0050] (4) The mixed powder in step (2) is flatly pressed on the surface of the titanium alloy substrate pretreated in step (3) to form a prefabricated layer with a thickness of 2 mm, and then a high entropy alloy coating is obtained by laser cladding; wherein the parameters of the laser cladding are: power P = 1100 W, scanning speed v = 300 mm / min, spot diameter D = 4 mm, defocus amount is 13 mm, and pure Ar gas is used as the protective gas in the cladding process, and the gas flow rate is 15 L / min.
[0051] Example 3
[0052] A multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating specifically comprises the following preparation steps:
[0053] (1) Weighing Al powder, Cu powder, and CoCrFeNi alloy powder to ensure that the molar ratio of Al:Cu:Co:Cr:Fe:Ni is 0.7:0.3:1:1:1:1; wherein the molar ratio of Co, Cr, Fe, and Ni in the CoCrFeNi alloy powder is 1:1:1:1;
[0054] The purity of the raw material powder is not less than 99.9wt.%, the powder particle size is 15μm, and all powders are spherical powders;
[0055] (2) The raw material powder was placed in a planetary high-energy ball mill and ball-milled for 10 h at a rotation speed of 120 rpm and a ball-to-material ratio of 4:1 to mix evenly; after the ball milling, it was dried at 80° C. for 1 h to obtain a mixed powder.
[0056] (3) Pretreatment of the titanium alloy substrate surface: Use 400 and 600 mesh sandpaper to polish the surface of the Ti-6Al-4V substrate to remove surface oxides and oil stains, then rinse and wipe with alcohol, and finally put the treated substrate into a drying oven at 60°C for 2 h for use.
[0057] (4) The mixed powder in step (2) is flatly pressed on the surface of the titanium alloy substrate pretreated in step (3) to form a prefabricated layer with a thickness of 1 mm, and then a high-entropy alloy coating is obtained by laser cladding; wherein the parameters of the laser cladding are: power P = 1100 W, scanning speed v = 300 mm / min, spot diameter D = 4 mm, defocus amount is 13 mm, and pure Ar gas is used as the protective gas in the cladding process, and the gas flow rate is 15 L / min.
[0058] Comparative Example 1
[0059] The preparation method of this comparative example is the same as that of Example 1, except that the raw material powder does not contain Cu powder; and the molar ratio of Al:Co:Cr:Fe:Ni is 1:1:1:1:1.
[0060] Comparative Example 2
[0061] The preparation method of this comparative example is the same as that of Example 1, except that the raw material powder does not contain Al powder; and the molar ratio of Cu:Co:Cr:Fe:Ni is 1:1:1:1:1.
[0062] Comparative Example 3
[0063] The preparation method of this comparative example is the same as that of Example 1, except that powders of Co, Cr, Fe and Ni are used in place of CoCrFeNi alloy powder in the raw material powder; wherein the molar ratio of Co, Cr, Fe and Ni is 1:1:1:1.
[0064] Experimental Example 1
[0065] 1. The titanium alloy substrate with coating prepared in Example 1, Comparative Example 1 and Comparative Example 2 was cut into rectangular samples of 20 mm × 10 mm × 10 mm by using electric spark wire cutting technology. The coated cut surface of the sample was polished with 240 mesh, 600 mesh, 800 mesh, 1200 mesh and 2000 mesh sandpaper to remove the oil stains and oxides on the surface until it was smooth. It was polished to a mirror surface with a silicon dioxide fine polishing liquid with a particle size of 0.12 μm, so that there were no obvious scratches on the surface. Finally, it was ultrasonically cleaned with anhydrous ethanol. Then the phase analysis was performed to obtain the XRD diffraction pattern as shown below: Figure 2 It can be seen that the phase structure of the coating prepared in Example 1 is a solid solution of FCC phase and BCC phase, and the structure is relatively simple.
[0066] 2. The mechanical properties of the high entropy alloy coating prepared in Example 1 were characterized. The hardness of the high entropy alloy coating prepared in Example 1 was as follows: Figure 4 As shown by Figure 4 It can be seen that Al with a dual-phase structure 0.7 CoCrCu 0.3 The hardness of the FeNi high entropy alloy coating is significantly higher than that of the substrate, and the average hardness of the cladding layer is 723.66HV 0.5 The average hardness of the matrix is 342.1HV 0.5 The coating hardness is 2.12 times that of the substrate, and the hardness is significantly improved.
[0067] At the same time, the hardness of the substrates with coatings obtained in Comparative Examples 1-3 was tested, and the average hardness of the cladding layers was 701.59 HV. 0.5 、694.70HV 0.5 、716.19HV 0.5 .
[0068] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating, characterized in that: Contains the following molar ratios of metal elements: Al:Cu:Co:Cr:Fe:Ni=0.7:0.3:1:1:1:1; The raw materials of Al and Cu are metal powders; the raw materials of Co, Cr, Fe and Ni are CoCrFeNi alloy powders; The molar ratio of Co, Cr, Fe and Ni in the CoCrFeNi alloy powder is 1:1:1:
1.
2. The method for preparing the multi-principal component Al-Co-Cr-Cu-Fe-Ni high entropy alloy coating according to claim 1, characterized in that: The following steps are involved: S1. Al powder, Cu powder and CoCrFeNi alloy powder were weighed according to the molar ratio and then ball-milled and mixed uniformly and dried to obtain a mixed powder; S2. performing surface pretreatment on the titanium alloy substrate; S3. The mixed powder is flatly pressed on the surface of the pretreated titanium alloy substrate, and then a high entropy alloy coating is obtained by laser cladding technology.
3. The preparation method according to claim 2, characterized in that: The purity of each powder in S1 is not less than 99.9wt.%, the powder particle size is 15-53μm, and the powder is spherical powder.
4. The preparation method according to claim 2, characterized in that: The ball milling mixing in S1 is carried out by a high-energy ball mill; the parameters of the ball milling are: rotation speed 120 rpm, time 10 h, and ball-to-material ratio 4:
1.
5. The preparation method according to claim 2, characterized in that: The drying process in S1 is carried out at a temperature of 80 to 100° C. and for a time of 1 to 2 hours.
6. The preparation method according to claim 2, characterized in that: The pretreatment method in S2 is: polishing the surface of the titanium alloy substrate with 400 and 600 mesh sandpapers in turn, then rinsing and wiping with alcohol, and finally putting the treated substrate into a drying oven at 60-80° C. for 1-2 hours for use.
7. The preparation method according to claim 2, characterized in that: The titanium alloy matrix in S2 is Ti-6Al-4V.
8. The preparation method according to claim 2, characterized in that: The thickness of the prefabricated layer of powder in S3 is 1 to 2 mm.
9. The preparation method according to claim 2, characterized in that: The laser cladding parameters in S3 are: power P=1100 W, scanning speed v=300 mm / min, spot diameter D=4 mm, defocusing amount is 13 mm, and pure Ar gas is used as the protective gas in the cladding process, and the gas flow rate is 15 L / min.
Citation Information
Patent Citations
Laser cladding method used for controlling producing of copper permeating cracks
CN109778180A
High-powder-yield mechanical alloying and sintering forming method for high-entropy alloy
CN113528925A
Shield tunnelling machine main bearing sealing runway remanufactured coating and preparation method thereof
CN113774375A
Gradient high-entropy alloy material and preparation method thereof
CN114622199A
Argon arc cladding high-entropy alloy coating and preparation method thereof
CN115976511A